PEMBUATAN TRAINER ON/OFF LAMPU MENGGUNAKAN SMS BERBASIS MIKROKONTROLER ARDUINO UNO ATMEGA328 - Destiarini; Risky Endar Subagja (Universitas Mahakarya Asia, 2019)
With busy activities, someone will have difficulty controlling electronic equipment at home, along with the progress of the control system can make it easier for a person to control a system remotely, not only between cities, even between islands within the scope of communication used. With the help of an AC voltage source equipment control system via SMS (Short Message Service), where later application users do not need to go to the switch box to be able to turn on the equipment, but only by sending a message to activate the desired equipment. The system that is formed consists of (Short Message Service) SMS and Arduino Uno ATMEG 328 as a database storage that will later be used as data storage messages sent by users, the database here is used as well as the message communication rate recorder used to match the type of message sent by activating the tool . When a user sends (Short Message Service) an SMS to activate a device, the data sent automatically enters the message database